Authority of Sultan Makmun al Rasyid Perkasa Alamsyah in Building Islamic Institutions in the Deli Sultanate - M Yakub; Ahmad Sampurna; Benny Munardi (Indonesian Journal of Islamic Literature and Muslim Society, 2022)
This research delves into the examination of the authority exercised by Sultan Ma'mun Al-Rasyid Perkasa Alamsyah in the establishment of Islamic institutions within the historical context of the Deli Sultanate spanning from 1817 to 1924. Employing a qualitative descriptive approach rooted in the study of history and civilization, this study sheds light on the notable achievements of Sultan Ma'mun Al-Rasyid in the realm of Islamic institutional development. Notable outcomes of this research include the enduring legacy of the Great Mosque of Al-Mashu'n and various other mosques that continue to thrive today. Furthermore, it highlights the Sultan's commitment to the implementation of Sharia policies within his domain, alongside his unwavering support for the clergy and mufti, thereby underscoring the pivotal role played by his authority in nurturing Islamic institutions during this period.